Tracheal replacement revisited: Use of a vascularized tracheal transplant in a porcine model. (26th December 2018) - Jacobson, Adam S.; Roden, Dylan F.; Lee, Eric Q.; Most, Allison; Meyers, Adrienne; Liu, Cheng; Levine, Jamie
Abstract : Objectives/Hypothesis: To determine if a long segment of trachea can be transplanted as a vascularized organ and to determine if a tracheal transplant is a potential surgical option for a long‐segment circumferential tracheal defect. Study Design: Animal model. Methods: Four (two donors and two recipients) adult domestic Yorkshire swine were used. Two sets of transplants were performed from a donor to recipient pig. The transplant was placed heterotopically (not in continuity with the airway), and the recipient animals were monitored for 14 days to ensure the transplants were well vascularized. Immunosuppressive therapies included methylprednisolone, cyclosporine, and azathioprine. Gross as well as histological examination of multiple tissues types including mucosa, cartilage, muscle, and blood vessels were performed postsacrifice on day 14. Results: Recipient animal weights ranged from 40 to 42 kilograms. Both recipient pigs survived the full 14 days of study and exhibited normal activity and appetite. Ischemia time of transplanted grafts ranged from 63 to 72 minutes. Transplanted tracheas included a minimum of 15 cartilaginous rings and measured greater than 10 cm in length. Both grafts maintained a robust blood supply throughout the duration of study. Conclusions: The entire visceral compartment can be reliably transplanted, either as a single component (trachea) or as a chimeric flap with multiple components (trachea, esophagus, larynx, and pharynx). Further studies in the swine model should be considered to study the effects of transplanting the trachea orthotopically into the native airway. Further studies are needed into the reliability of this technique of transplantation in humans. Level of Evidence: NA Laryngoscope, 128:S1–S9, 2018